Creation to Revelation : a brief account of the biblical story - Chatham, James O., 1937-- (Grand Rapids, Michigan : William B. Eerdmans Publishing, 2006)
"We know the stories - Adam and Eve, David and Goliath, Jesus feeding the five thousand. We know the verses - John 3:16, Psalm 23, 1 Corinthians 13. But how many of us can take the separate pieces and fit them into the Bible as a whole? With the common practice of taking passages out of context, even active Bible readers tackling a chapter or more every day can easily lose sight of the whole biblical story." "James Chatham, a beloved minister and Bible teacher, has spent decades offering the panorama of Scripture from Genesis to Revelation to those who want to understand God's Word more fully. He now spreads the wealth in this practical volume. In twenty-six short segments designed to facilitate Bible study, Creation to Revelation weaves the disparate stories and familiar verses into a complete narrative and thematic framework, taking "the whole counsel of God" into account. Pertinent sidebars, carefully designed discussion questions, and two helpful appendixes - a chronology of the Bible's story and select daily Bible readings - enhance Chatham's overview. Extremely accessible to a wide audience, this pithy book is meant not to replace the Bible but rather to lure us into reading it - and to help us better understand its message. Book jacket."--BOOK JACKET
Appendix B : daily Bible readings
Includes index
Keywords: Bible -- Criticism, interpretation, etc; Bible -- History of biblical events